MENJADI ADAPTIF: STRATEGI BIRO PERJALANAN WISATA OBAJA TOUR MENGHADAPI KRISIS PANDEMI COVID-19 - Nurul Hasanah Fidya; I Made Adhi Gunadi; Yosi Erfinda (Fakultas Pariwisata Universitas Pancasila, 2022)
As a result of the COVID-19 pandemic, many business sectors have been disrupted, including the tourism business which hitted the most. This research aim to examine the strategy of Obaja Tour as one of established travel agencies in dealing with the crisis during the COVID-19 pandemic. The type of research used is qualitative methods with a descriptive analysis approach. The data collection obtained by conducting interviews, literature study, and observation. The collected data was validated by triangulation method. The findings show that Obaja Tour managed to survive and still does their function as a travel agency during the pandemic. Obaja Tour is currently in the Resolution and Feedback stage, by continuing to carry out activities such as previous operations and using Adaptive Strategies to facing the crisis through making slight modifications of the company's operations by creating new types of business such as Health Care, Food Service, and Cycling Equipment. Keywords: Covid-19, pandemic, crisis management, travel agency.